Expression and Localization of Cathepsins B, D, and G in Two Cancer Stem Cell Subpopulations in Moderately Differentiated Oral Tongue Squamous Cell Carcinoma - Featherston, Therese; Marsh, Reginald Walter; van Schaijik, Bede; Brasch, Helen D.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Medicine, 2017)
Aim We have previously demonstrated the putative presence of two cancer stem cell (CSC) subpopulations within moderately differentiated oral tongue squamous cell carcinoma (MDOTSCC), which express components of the renin-angiotensin system (RAS). In this study, we investigated the expression and localization of cathepsins B, D and G in relation to these cancer stem cell (CSC) subpopulations within MDOTSCC. Methods 3,3-Diaminobenzidine (DAB) and immunofluorescent (IF) immunohistochemical (IHC) staining was performed on MDOTSCC samples to determine the expression and localization of cathepsins B, D and G in relation to the CSC subpopulations. NanoString analysis and colorimetric in-situ hybridization (CISH) were used to study their transcripts expression. Enzyme activity assays were performed to determine their activity in MDOTSCC. Results IHC staining demonstrated expression of cathepsin B, D and G in MDOTSCC. Cathepsins B and D were localized to CSCs within the tumor nests, while cathepsins B was localized to the CSCs within the peri-tumoral stroma, and cathepsin G was localized to the tryptase+ phenotypic mast cells within the peri-tumoral stroma. NanoString and CISH analyses confirmed transcription activation of cathepsins B, D and G. Enzyme activity assays confirmed active cathepsins B and D, but not cathepsin G. Conclusions The presence of cathepsins B and D within CSCs and cathspsin G within phenotypic mast cells suggest bypass loops for the RAS as potential novel therapeutic targets for MDOTSCC.